A first dictionary of cultural literacy : what our children need to know - Hirsh, E. D. (Houghton Mifflin, 1989)
"Presents an outline of the knowledge that should be acquired by the end of sixth grade, according to Cultural Literacy Foundation in such categories as literature, religion and philosophy, history, geography, mathematics, science and technology"--Verso tp.